Adaptation Relationship Between Water Resource Utilization and Economic Development in Jiangxi Province - Wang Fei; Mu Yaqing; Tian Pei; Hao Fanghua; Chen Shu; Wu Yijin (Shuitu baochi tongbao)
[Objective] The adaptation relationship and the changing trends between total water consumption and total GDP, water consumption of three industries and GDP of corresponding industries in Jiangxi Province and its 11 prefecture-level cities from 2015 to 2020 were studied, revealing the reasons for the adaptation differences, and providing scientific basis for the coordination of water resource utilization and economic development in the region. [Methods] Industrial water consumption and industrial GDP data were used with the Tapio model in this study. [Results] Total water use and total GDP of Jiangxi Province were both in a state of adaptation from 2015 to 2020, showing a trend pattern of “strong adaption—expanded adaption—strong adaptation”. The degree of adaptation exhibited a spatial distribution pattern of northwest > south > central and east. Agricultural water consumption and GDP of the primary industry showed a trend pattern of “adaptation—coupling—adaptation”, while the adaptation relationship for each city fluctuated. Except for the expansionary adaptation between industrial water consumption and GDP for the secondary industry in the province in 2018—2019, there was a strong adaptation relationship in other periods, and all cities reached a strong adaptation state in 2017—2018. The tertiary industry of the entire province was in a state of expansionary adaptation and positive coupling from 2015 to 2020. Except during the pandemic period in 2020, the adaptation of most cities was better than that of agriculture from 2015 to 2019. On the whole, the degree of adaptation between industrial water consumption and industrial GDP in Jiangxi Province followed the order of industry > tertiary industry > agriculture. [Conclusion] The main reasons for the change in the adaptation relationship between water use and economic development were precipitation, economic level, policy measures, industrial structure, technological progress, construction of water conservation facilities, etc. Countermeasures, such as developing special industries according to local conditions, determining production with water, and promoting transformation and upgrading of industrial structure, have been proposed to help promote sustainable development in Jiangxi Province.